Development and analysis of wearable textile antenna (WTA) design for ISM and hiperlan applications - Nurul Husna, Mohd Rais (Universiti Malaysia Perlis (UniMAP), 2014)
In recent years, there has been growing interest in utilizing wearable textile antennas for Body Area Network (BAN) antenna applications. Availability of conductive textiles allowed manufacturing of light-weight and flexible wearable antennas made entirely out of textiles. The proposed antenna is designed and optimized for both ISM (Industrial, Science and Medical) and HiperLAN (High Performance Radio LAN) applications, where operating frequency ranges from 2400 to 2480 MHz and 5150 to 5750 MHz, respectively. Previously, conventional microstrip antenna designs fabricated using rigid printed circuit board (PCB) laminates are unable to conform to BAN's flexibility and deformity prerequisites. On the contrary, the proposed antenna in this investigation is fabricated using conductive textiles, which are built using a combination of conductive polymer/metal fibers and normal fibers. The development procedure of this Wearable Textile Antenna (WTA) starts with its specification definition, materials selection, simulation using CST Microwave Studio software and finally, design prototyping and measurements. Due to the manual fabrication procedure employed, the antenna designed is to be as simple as possible. The proposed basic rectangular radiator is then improved using slots and slits to enable dual-band resonance and broad bandwidths. Its main structural design concept is based on a suspended plate antenna - a 60 × 45 mm rectangular radiating element is suspended over a 80 × 60 mm ground plane using a 5 mm foam substrate. The antenna has undergone several investigations to ascertain its overall performance. Performance of the antenna investigated in free space, placements on different body locations and under different bending radii. S11, gain and efficiency of the antenna in free space and in proximity of human body showed good agreements, indicating design robustness under various operating conditions.